Β1 integrin monoclonal antibody treatment ameliorates cerebral cavernous malformations. Issue 12 (9th November 2022) - McCurdy, Sara; Lin, Jenny; Shenkar, Robert; Moore, Thomas; Lightle, Rhonda; Faurobert, Eva; Lopez‐Ramirez, Miguel‐Alejandro; Awad, Issam; Ginsberg, Mark H.
Abstract: β1 integrins are important in blood vessel formation and function, finely tuning the adhesion of endothelial cells to each other and to the extracellular matrix. The role of integrins in the vascular disease, cerebral cavernous malformation (CCM) has yet to be explored in vivo. Endothelial loss of the gene KRIT1 leads to brain microvascular defects, resulting in debilitating and often fatal consequences. We tested administration of a monoclonal antibody that enforces the active β1 integrin conformation, (clone 9EG7), on a murine neonatal CCM mouse model, Krit1 flox/flox ;Pdgfb‐iCreERT2 ( Krit1 ECKO ), and on KRIT1‐silenced human umbilical vein endothelial cells (HUVECs). In addition, endothelial deletion of the master regulator of integrin activation, Talin 1 (Tln1), in Krit1 ECKO mice was performed to assess the effect of completely blocking endothelial integrin activation on CCM. Treatment with 9EG7 reduced lesion burden in the Krit1 ECKO model and was accompanied by a strong reduction in the phosphorylation of the ROCK substrate, myosin light chain (pMLC), in both retina and brain endothelial cells. Treatment of KRIT1‐silenced HUVECs with 9EG7 in vitro stabilized cell–cell junctions. Overnight treatment of HUVECs with 9EG7 resulted in significantly reduced total surface expression of β1 integrin, which was associated with reduced pMLC levels, supporting our in vivo findings. Genetic blockade of integrin activation by Tln1 ECKO enhanced bleeding and did not reduce CCM lesion burden in Krit1 ECKO mice. In sum, targeting β1 integrin with an activated‐specific antibody reduces acute murine CCM lesion development, which we found to be associated with suppression of endothelial ROCK activity.